SOCIATRY OF MORENO: ONLINE SOCIODRAMA AND SOCIATRY FOR SOCIAL CRISES - Deniz Altinay (Revista Brasileira de Psicodrama, 2023)
In this article, Sociatric and Sociodramatic systems of J.L. Moreno, the founder of the Psychodrama Group Psychotherapy system, are discussed in the context of online applications. With the pandemic, war and other social crises online psychological help has been needed more than ever. There is a need to heal not only the individual, but also large groups and an entire society in such a great social trauma. Moreno is a scientist who wants to achieve this goal with his discipline of sociatry and he is the father of the concept of sociatry. Sociatry is concerned with the healing of societies. In this article, you will find an online intervention that involve a group of professionals with sociatric applications. With the help of online sociodrama studies, we were able to manage crisis intervention work with the affected group. To heal the society is to protect the future of humanity. Moreno, as a great visionary, is a genius who saw this truth a hundred years ago